Kontekstualisasi Kemaritiman dalam Desain Framework Sistem Pembelajaran Bahasa Indonesia - Juwintar Febriani Arwan; Laksmi Dewi; Asep Herry Hernawan (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
One of the characteristics of the Kurikulum Merdeka policy is that it gives freedom for teachers to develop learning paths and subject matter. This is intended to create meaningful and contextual learning with students' daily lives. This study aimed to design Indonesian language learning that is in line with maritime literacy. Development of learning using the Dick and Carrey model. The results of the learning design showed that the learning design is in accordance with the learning objectives and achievements. Continuous development and improvement still needs to be done to produce contextual learning and can be used to increase ocean literacy capacity